A role for the subthalamic nucleus in response inhibition during conflict. - Brittain, J; Watkins, K; Joundi, R; Ray, N; Holland, P; Green, A; Aziz, T; Jenkinson, E (Society for Neuroscience, 2012)
The subthalamic nucleus (STN) is a key node in the network that supports response inhibition. It is suggested that the STN rapidly inhibits basal ganglia activity, to pause motor output during conflict until an appropriate motor plan is ready. Here, we recorded neural activity during a Stroop task from deep brain stimulation electrodes implanted in the human STN. We intended to determine whether cognitive psychological phenomena such as the Stroop effect can be explained via mechanisms of response inhibition involving the STN, or whether higher cognitive centers are alone responsible. We show stimulus-driven desychronization in the beta band (15-35 Hz) that lasts throughout the verbal response, in keeping with the idea that beta-band synchrony decreases to allow motor output to occur. During incongruent trials--in which response times were elongated due to the Stroop effect--a resynchronization was seen in the beta band before response. Crucially, in the incongruent trials during which the participant was unable to withhold the prepotent response, this resynchronization occurred after response onset. We suggest that this beta-band resynchronization pauses the motor system until conflict can be resolved.